2017
DOI: 10.1007/s40496-017-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Oral Microbiome and Dental Caries

Abstract: Purpose of Review Our paper reviews how dietary changes during human evolution have contributed to the increased incidence and prevalence of dental caries in modern populations by shifting the oral microbiome from a 'healthy' to 'carious' state. We addressed two questions: (1) what is the microbial difference between the states of health and caries, and (2) how has the development of an agricultural diet impacted the oral microbiome? Recent Findings The application of Next-Generation Sequencing has revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These associations do not prove cause and effect, and it is more likely that high counts of these organisms are due to high sugar diets, in which sense they reflect caries risk and are not necessarily the only drivers of the disease process [29]. Indeed modern approaches to microbiomics, involving next generation sequencing methods, imply that complex consortia of bacteria are so associated, and these may be pathogenic [30, 31]. Today, growth of these consortia, composed of commensal species, is regarded as the result of ecological shifts driven by changes in the environment [32, 33], such that a range of ecological approaches to caries prevention are now being explored [34].…”
Section: Discussionmentioning
confidence: 99%
“…These associations do not prove cause and effect, and it is more likely that high counts of these organisms are due to high sugar diets, in which sense they reflect caries risk and are not necessarily the only drivers of the disease process [29]. Indeed modern approaches to microbiomics, involving next generation sequencing methods, imply that complex consortia of bacteria are so associated, and these may be pathogenic [30, 31]. Today, growth of these consortia, composed of commensal species, is regarded as the result of ecological shifts driven by changes in the environment [32, 33], such that a range of ecological approaches to caries prevention are now being explored [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the biofilm growth phase is referred to as the remodeling phase, which is characterized by early dominance by the genus Streptococcus followed by a shift toward more anaerobic and filamentous flora [53]. Hence, over time, the cariogenic biofilms will change, as cells are dying or changing their properties because of ecological pressure [62].…”
Section: Resultsmentioning
confidence: 99%
“…regularity of sugar intake) likely varying depending on the prevailing oral microbiota. 22,43 High prevalence of occlusal caries is associated with low attrition, while interproximal lesions are linked with high attrition. 44 However, interproximal caries may also be related to calculus, as a result of plaque deposition in these areas 45 , although this link has not been extensively researched.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is often suggested that caries was scarce in pre-agricultural hominins. 21,22 Yet, evidence for such lesions in pre-agricultural groups is growing. [23][24][25][26][27][28][29][30][31] In light of this evidence, we reanalysed South African fossil hominin material and Homo naledi recorded for the first time for the presence of caries.…”
Section: Introductionmentioning
confidence: 99%